Establishment of quantitative indicators for an efficient treatment on masticatory muscle pain - Sunhee Lee; Hye‐Min Ju; Donald Ho; Byong‐Sop Song; Sung‐Hee Jeong; Yong‐Woo Ahn; Soo‐Min Ok; Kyounga Cheon (Wiley, 2023)
Abstract Background Although several studies have investigated effective treatments for masticatory muscle pain (MMP), no unified conclusion has been drawn regarding the effectiveness of these treatments. Objectives This study aimed to define quantitative indicators for predicting the outcome of MMP treatment. Materials and Methods In total, patients aged 20-70 years were recruited and divided into the MMP (n = 24) and control (n = 36) groups, based on the presence of MMP according to the Diagnostic Criteria for Temporomandibular Disorders. At pretreatment, the MMP group was assessed using quantitative indicators such as subjective pain levels, pain duration, graded chronic pain scale (GCPS), and perceived stress scale (PSS). Salivary alpha‐amylase (sAA) and interleukin‐6 (IL‐6) levels were analyzed. The masticatory muscle palpation score and the range of mouth opening were measured. At posttreatment, subjective pain levels, mouth opening, and treatment/medication duration were examined. The PSS and sAA levels were assessed in the control group. Results sAA levels in the MMP group were significantly higher than those in the control group (p < .05). The masseter muscle palpation score (MPS) showed a positive correlation with IL‐6 levels (ρ = 0.503, p < .05) and a negative correlation with nonsteroidal anti‐inflammatory drug (NSAID) treatment period (ρ = −0.462, p < .05). The temporalis muscle palpation score (TPS) was positively correlated with pain duration and GCPS grade (ρ = 0.483, p < .05, and ρ = 0.445, p < .05, respectively). Conclusions Treatment with NSAIDs was effective in the MMP group with high MPS and IL‐6 levels, but not in the MMP group with high TPS, pain duration, and GCPS grade.